(3GdCLhHI GdebfYI aj GdeSGFd GdefhYIs
(3ChdgG (B:s
(3GdMeO Gddg GdefaQO HGdEjLGO hGdENJjGQ dEJUGag HGdUaGJ GdefGSHI ddJCKjQ hENJdGa GdBKGQ s
(3BNQgG (B:s
(3bGd eDdag YaG Gddg Yfg gPG GdZQV ef GdCLhHI GfJgi HMeO Gddg hMSf Yhfg hUdi Gddg Ydi eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs